El trabajo remoto y su relación con la productividad de una empresa tecnológica en Lima - Muro Olivera, Elsa Del Pilar (2023)
The purpose of this research paper is to determine the relationship between remote work and productivity, in the context of the COVID-19 pandemic, in the company Indra Perú S.A. Lima, in the year 2021. The methodology used is descriptive, cross-sectional, correlational with a non-experimental design. The market research was carried out through a survey applied to 314 employees of the company, resulting in a Spearman coefficient of 0.905, which is positive and significant, demonstrating that there is a relationship between remote work and productivity. Therefore, the study concludes that the productivity of the employee working remotely can be equal or better than working in a 100% face-to-face manner in their workplace.